The range of congenital malformations associated with cleft lip and palate. - Duarte, R (1999)
The congenital malformations associated to cleft lip and cleft palate cover a wide range of pathologies with incidence and acuteness that vary according to the authors. In the 284 patients followed and/or referred to the Cleft Consultation of Dona Estefânia Hospital, 78 had associated malformations (27.5%). In three cases there was consanguinity in parents. A familial incidence of cleft and/or other congenital malformations was found in 13 and 10 patients respectively. Thirty patients had malformative syndromes. In the remaining 48, 127 associated congenital malformations (M.C.A.) were identified, in accordance with the Smith criteria, 81 major and 46 minor. The most frequent associated malformations are those of the face (25.9%) and of the cardiovascular system (16.5%). The multiple anomalies (of various systems) are the most frequent (47.9%), followed by the isolated anomaly (29.1%) and the multiple of one system (22.9%). In what concerns the association of syndromes with the type of cleft, primary, secondary or total palate, those of the secondary were the most frequent, particularly that of the Pierre Robin sequence (S.P.R.)--19 in 36 secondary cleft palate.